Dinosaurs! - Gibbons, Gail. (New York : Holiday House, 2008)
Simple text and illustrations introduce the characteristics and habits of a variety of dinosaurs.
Booklist.
Horn Book.
Kirkus Review.
3.9
K-3
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Dinosaurs